Mitogen-activated protein kinase kinase 7 in inflammatory, cancer, and neurological diseases - Caliz, Amada D.; Vertii, Anastassiia; Fisch, Vijay; Yoon, Soonsang; Yoo, Hyung-Jin; Keaney, John F.; Kant, Shashi (Frontiers in Cell and Developmental Biology, 2022)
Stress-activated mitogen-activated protein kinase kinase 7 (MKK7) is a member of the dual-specificity mitogen-activated protein kinase family. In the human body, MKK7 controls essential physiological processes, including but not limited to proliferation and differentiation in multiple tissues and organs. MKK7, along with the MKK4 pathway, has been implicated in stress-activated activities and biological events that are mediated by c-Jun N-terminal kinase (JNK) signaling. Although numerous studies have been performed to identify the role of JNK in multiple biological processes, there are limited publications that focus on dissecting the independent role of MKK7. Recent research findings have spurred testing via in vivo genetically deficient models, uncovering previously undocumented JNK - independent functions of MKK7. Here we discuss both JNK - dependent and - independent functions of MKK7 in vivo. This review summarizes the role of MKK7 in inflammation, cytokine production, cancer, and neurological diseases.